European stabilization policy after the Covid-19 pandemic: More flexible integration or more federalism? - Fredrik N. G. Andersson; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2022)
Crises are a major driving force behind cooperation in the European Union. This holds also for monetary and fiscal policy. During severe crises, cooperation has been enlarged and intensified. The recent covid-19 pandemic is a clear example of this pattern. The pandemic has had huge impact on the conduct of stabilization policies in the EU. Public debt has grown rapidly in many EU member states. The ECB has carried out a highly expansionary monetary policy. In this paper, we discuss the implications for the EU of a move towards increased fiscal federalism following the pandemic. First, the role of crises as a driver of political change is analysed. Next, we examine in greater detail, the effect of crises on the design of stabilisation policies in the EU since the introduction of the euro, the common currency. Finally, we discuss the significance of the recent pandemic-induced steps towards increased federalism for the EU. We raise the question as to whether this is a desirable path for the future of European cooperation.
Keywords: E6; F42; H6; 330; Monetary policy; fiscal policy; fiscal rules; stabilization policy; European Union; ECB; crises